2011
DOI: 10.3109/14767058.2011.569613
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status of pregnant women in Shanghai, China

Abstract: Vitamin D deficiency and insufficiency were common in pregnant Chinese women and routine screening as well as prophylactic measures should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
27
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 15 publications
3
27
2
Order By: Relevance
“…26 Several studies from our neighbouring countries confirmed the vitamin D deficiency; for instance, two cross-sectional studies conducted in Shanghai, China found that majority of the PW (69%) had vitamin D deficiency with mean level of 17.57 ±11.44 ng/ml. 27 A study from India found that high prevalence of physiologically significant hypovitaminosis D among PW and their newborns. 28 In Bangladesh, hypovitaminosis D is common in women regardless of age, lifestyle and clothing.…”
Section: Discussionmentioning
confidence: 99%
“…26 Several studies from our neighbouring countries confirmed the vitamin D deficiency; for instance, two cross-sectional studies conducted in Shanghai, China found that majority of the PW (69%) had vitamin D deficiency with mean level of 17.57 ±11.44 ng/ml. 27 A study from India found that high prevalence of physiologically significant hypovitaminosis D among PW and their newborns. 28 In Bangladesh, hypovitaminosis D is common in women regardless of age, lifestyle and clothing.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the judgment standards used in China take VD above 30 ng/ml as the best level, below 20 ng/ml as VD insufficiency while VD below 12 ng/ml is diagnosed as VD deficiency [10]. According to the above judgment standards in China, VD level in Chinese people is generally low and the rates of adult VD deficiency in different regions are all above 50% [1719]. Therefore, China’s Guide for Healthy Application of Vitamin D in Adult Skeleton in 2014 pointed out that for people who are in VD insufficiency, deficiency and not easy to supplement VD from food or sunlight and other physiologic ways, they should make appropriate daily VD supplement to prevent the occurrence of calcium deficiency, osteoporosis and other diseases [10].…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes of pregnant women, fetuses and live births grouped according to vitamin D status Two cross-sectional studies with small sample sizes conducted in Shanghai22 (located 31.1ºN) and Chengdu 23 (located 30.…”
mentioning
confidence: 99%